PENINGKATAN KESADARAN MASYARAKAT TERHADAP KEBERSIHAN LINGKUNGAN MELALUI KEGIATAN GOTONG ROYONG DI DESA ANA ENGGE - Martha Kaka; Chindy Hanggara Rosa Indah (Jurnal Dremi (Demi Pengabdi Masyarakat), 2026)
Environmental cleanliness is an essential aspect of creating a healthy, comfortable, and sustainable living environment. However, public awareness of maintaining environmental cleanliness remains relatively low in many rural communities, including Ana Engge Village. This Community Service Program Based on Local Potential (PMBP) aimed to improve community awareness and participation through community clean-up activities involving Field Experience Program (PPL) students. The program employed a participatory approach consisting of environmental observation, coordination with village authorities, community clean-up activities, environmental greening, provision of waste disposal facilities, and program evaluation. The activities were conducted over two months with the active involvement of village officials, local residents, and university students. The results demonstrated increased community participation in maintaining environmental cleanliness, improved environmental awareness, and cleaner village surroundings. Furthermore, collaboration among students, village government, and the community strengthened the culture of mutual cooperation as social capital for sustainable rural development. The program indicates that participatory community empowerment effectively enhances environmental awareness and encourages sustainable environmental management.